PENGARUH PENERAPAN SISTEM E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN PEMAHAMAN INTERNET SEBAGAI VARIABEL PEMODERASI DI KOTA MALANG - Iva Yuliana Pratama; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2020)
This study aims to determine the effect of implementation the e-filing system to taxpayer compliance with internet understanding as a moderating variable in Malang. The data is primary data and the population is Tax Service Office in Malang. The sample are 100 respondents by purposive sampling method. The existence of this research is expected to be able to add and develop insights, information, as well as thinking and science that are particularly related to the research topic. The results of this study indicate that (1) Simultaneous research proves that the independent variables influence simultaneously or jointly on the dependent variable. (2) Partial research proves that the independent variable, namely the application of the e-filing system, has a positive and significant effect on taxpayer compliance. This means that the higher the application of the e-filing system that is applied at the North Malang Pratama Tax Service Office, the higher the level of tax compliance. (3) Research shows that internet understanding variables can moderate the effect of applying e-filing systems to taxpayer compliance. This means that the higher the internet understanding of taxpayers towards the internet that supports the implementation of e-filing systems in the North Malang Pratama Tax Service Office can improve the level of tax compliance. Keyword: Application of e-filing systems, tax compliance, internet understanding